2015
DOI: 10.1038/srep12512
|View full text |Cite
|
Sign up to set email alerts
|

An in silico platform for predicting, screening and designing of antihypertensive peptides

Abstract: High blood pressure or hypertension is an affliction that threatens millions of lives worldwide. Peptides from natural origin have been shown recently to be highly effective in lowering blood pressure. In the present study, we have framed a platform for predicting and designing novel antihypertensive peptides. Due to a large variation found in the length of antihypertensive peptides, we divided these peptides into four categories (i) Tiny peptides, (ii) small peptides, (iii) medium peptides and (iv) large pept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
99
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(107 citation statements)
references
References 40 publications
0
99
0
Order By: Relevance
“…In their QSAR approach developed with ACE inhibitory peptides, Kumar, et al 49 have also included negative datasets to develop classication models in order to assign unknown peptides to a category of active or inactive peptides. These models have been incorporated in a freely available web resource (http:// crdd.osdd.net/raghava/ahtpin).…”
Section: Limitations Of Qsar For the Study Of Bapsmentioning
confidence: 99%
See 2 more Smart Citations
“…In their QSAR approach developed with ACE inhibitory peptides, Kumar, et al 49 have also included negative datasets to develop classication models in order to assign unknown peptides to a category of active or inactive peptides. These models have been incorporated in a freely available web resource (http:// crdd.osdd.net/raghava/ahtpin).…”
Section: Limitations Of Qsar For the Study Of Bapsmentioning
confidence: 99%
“…Several QSAR approaches have suggested that specic scales allowed obtention of QSAR models with higher correlation and cross-validation coefficients (R 2 and Q 2 , respectively), which has generally been the case with the more recently developed amino acid descriptor scales. 37,39,49,83,84 Some QSAR studies incorporating relatively large numbers of BAPs in the dataset have been conducted with bioactivity data obtained using different experimental conditions (enzyme : substrate ratio, source of enzymes, substrate, temperature, etc. ), which makes the validity of the models developed questionable.…”
Section: Limitations Of Qsar For the Study Of Bapsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Enzyme Predictor tool was used to help to analyze peptide sequences[21]. The QSAR platform AHT pin was used to predict antihypertensive Capacity in the variable length mode and amino acid composition model (SVM threshold was set to 0.9)[22]. …”
Section: Methodsmentioning
confidence: 99%
“…Due to this reason, the proteins or their evolutionary profiles first have to be reduced to a definite set of features to enable their usage in a computational predictive model . Main summary features traditionally used for function prediction have been (a) amino acid composition of the sequence (see eg, ), (b) dinucleotide or higher k‐mer frequencies, (c) column averages of a position‐specific substitution matrices, representing evolutionary profile or submatrices from a PSSM collected by pooling together rows where the same amino acid residue has been observed . Recently, we extended this feature set by defining sequence features in terms of predicted scores of binding with other ligands' binding sites for each residue in a protein .…”
Section: Introductionmentioning
confidence: 99%